Análise da sustentabilidade da suinocultura em uma unidade de producão familiar no município de Toledo - PR - Engelsing, Eliane Fátima (2019)
Family farming has been considered the model of production that best fits the principles of sustainable development, because of its importance in the absorption of employment, in the production of food, in social and economic functions. This research aimed to understand the sustainability of family farming in the municipality of Toledo, through a case study of a family unit focused on pig production. The work was organized in the form of articles. The first one measures the three main pillars of sustainability, using the IDEA method, which showed, through the score of the indicators, that there is a balance between the three pillars, but what stood out the most was the social pillar. The second article describes the economic part of the main activity developed in the property, which is swine farming. Based on the contractual modalities exercised by the companies, it was sought to compare the contract used by the property analyzed with another contractual modality, in order to analyze which would be the most economically advantageous for the rural producer. The results were then submitted to the analysis of the FOFA matrix, arriving at the conclusion that the contractual modality practiced by the property is more economically viable, in addition to providing greater autonomy in the form of pig production.